Impact of Service Learning in Engineering Education – A Case Study - Naik, Santosh Madeva; Bandi, Surendra (Journal of Engineering Education Transformations, 2025)
In the 21st Century, significant number of students have access to the tools for digital learning and spending most of their time on the internet and other social media platforms. Our college core philosophy is “Doing Engineering” rather than just studying engineering. In this context, EPICS (Engineering Projects in Community Service), UBA (Unnat Bharat Abhiyan), EWB (Engineers without Borders), GCSP (Grand Challenges Scholar Program) have been introduced to promote the learning through service. The above service learning which encourages students to work with local communities. and NGOs. real-time problem faced by the communities are identified by following design thinking approach. EPICS originated from Purdue University, USA. HITAM has been sprinting the EPICS program for the past five years. All freshmen engineering students enroll into EPICS Program as a mandatory course. To work on the realtime problems, multidisciplinary teams are formed for doing the community-based projects to enhance communication skills, technical knowledge, teamwork, presenting skills, and other traits along with progress in data analysis which will be unfolded in this paper. Forming the multidisciplinary teams in the beginning of the process has become a hindrance because students are separated discipline wise in the classrooms. To overcome this setback, a google form is created which consists of questions about interesting areas, technical knowledge and circulated among all the students for recording responses and area of interest. Subsequently, a meeting is called for all students and kindled their design thinking activity among the multidisciplinary teams as well. A strict line structure is followed to adapt design thinking methodology for implementing the EPICS course in the curriculum.